The Role of Knowledge, Creativity and Self-Confidence in the Performance of High School Prinsipals Using SEM-SmartPLS Analysis - Melky Malingkas; Kosmas Sobon; Jelvi M. Mangundap; Zhuldiz Anay (International Journal of Pedagogy and Teacher Education, 2024)
Effective leadership hinges on knowledge, creativity, and self-confidence in dynamic school environments. This study examines the contribution of these traits to high school principals' performance in leadership. Employing a quantitative approach, a survey was conducted with 75 respondents selected from a population of 308 using random sampling. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS software version 3.0, allowing in-depth exploration of the relationships between knowledge, creativity, self-confidence, and performance. The findings reveal that knowledge contributes 45%, creativity 30%, and self-confidence 25% to leadership effectiveness, collectively accounting for 87.5% of the variance in performance among school principals. Principals with strong knowledge, creativity, and self-confidence are better equipped to implement innovative strategies, motivate staff, and achieve educational goals. This study underscores the importance of professional development programs to enhance these attributes, emphasizing creativity and decision-making skills. Such initiatives can better prepare principals to navigate the complexities of modern educational leadership, including curriculum changes, resource constraints, and technological advancements. The research offers actionable insights for policymakers, educators, and administrators aiming to improve school leadership quality. It also highlights the mediating role of self-confidence in translating knowledge and creativity into practical leadership actions. These findings contribute to the broader discourse on leadership in education and provide a foundation for future studies to explore additional factors influencing principals’ performance.